Evaluation of Complications in Children after Liver Transplantation: A Single Centre Study (Journal of Fatima Jinnah Medical University, 2018)
Objective: To evaluate complications in children after liver transplantation so an early referral and appropriate management could be instituted to improve the late outcome.Study Design: Retrospective observational study.Place and Duration of Study: The study was carried out at the Department of Pediatric Gastroenterology, Hepatology & Nutrition, KFSH&RC, Jeddah, Kingdom of Saudi Arabia. The data between 1/10/2006 and 1/10/216 was included and analysed.Materials and Methods:Sample Size: 15 patients fulfilled the criteria of selection and were recruited in the study.Sampling Technique: The data was collected from the hospital’s electronic records: power chart system.Data Collection Procedure: A spread sheet was designed to collect data regarding demographics, primary diagnosis, long-term morbidity such as drug related complications, viral and bacterial infections, recurrence of cholestasis and primary disease, lympho-proliferative disease and graft versus host disease.Data presentation: The data was presented in percentages and frequencies in the form of charts and a table.Results: Among 15 children 12 were males, male to female ratio was 4:1. The median age at liver transplant was 2.5 years. Eight patients (53%) had either one or more episodes of bacterial infections, in the form of UTI, Sepsis, and throat infection. Five children (34%) developed EBV infection and 3 (20%) had CMV infection. Hypomagnesaemia was found in 14 (93%) children, while hyperphosphataemia and hypophosphatemia were noted in 9 (60%) and 5(33%) children respectively. Three (20%) children developed renal failure. Two (13%) children had recurrence of cholestasis, 1 (7%) child developed biliary stricture and another (17%) had chronic rejection. Only one child expired and the overall survival rate was 93%.Conclusion: Infections and drugs related electrolyte abnormalities were the most common complications noted in children, 6 months after liver transplantation. With early detection and appropriate management, majority of complications could be detected and managed, which would have an impact on the long term survival.
Keywords: Liver transplantation, Complications, Infections, Drugs, Electrolytes